Ανασκόπηση των ναυτιλιακών κύκλων - Χριστοδούλου, Γεώργιος (Τμήμα Εμπορίου, Χρηματοοικονομικών και Ναυτιλίας, Σχολή Διοίκησης και Οικονομίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
The aim of this work was to study the history of the shipping cycles in order to understand the functioning of the shipping markets, as well as the development of the shipping cycles in the shipping industry in general. The understanding of the past gives a competitive advantage to shipping companies, because yesterday’s knowledge will enable a company to become more efficient today in terms of cost, speed and service. From the whole study, it was found that there has been a sequential and continuous reduction of the research work for this specific field over time. While it would be normal for the articles dealing with the matter to increase in terms of research because of the importance of the subject, they are decreasing. This is certainly a negative fact that does not promote the subject, so there should be a direct differentiation referring to the increase of the academic articles, in order to draw more and more meaningful conclusions in the future on the issue so as to further improve its use by the shipping companies. The study also concludes that all research studies sought to link the shipping cycles to the competitiveness and efficiency of the shipping companies and to provide guidelines for the future to the shipping companies and also to avoid negative impacts.
Keywords: Shipping cycles; Shipping industry; Shipping market; Competitive advantage; Ναυτικοί κύκλοι; Ναυτιλία; Ναυτιλιακή αγορά; Ανταγωνιστικό πλεονέκτημα